Factors influencing the speed of cancer diagnosis in rural Western Australia: A General Practice perspective - Jiwa, Moyez; Halkett, Georgia; Aoun, Samar; Arnet, Hayley; Smith, Marthe; Pilkington, M.; McMullen, C. (BioMed Central Ltd., 2007)
Introduction. The speed of diagnosis impacts on prognosis and survival in all types of cancer. In most cases survival and prognosis are significantly worse in rural and remote Australian populations who have less access to diagnostic and therapeutic services than metropolitan communities in this country. Research suggests that in general delays in diagnosis were a factor of misdiagnosis, the confounding effect of existing conditions and delayed or misleading investigation of symptoms. The aim of this study is to further explore the factors that impact on the speed of diagnosis in rural Western Australia with direct reference to General Practitioners (GPs) working in this setting.